Application of Good Governance Principles in Public Services in Matakali District, Polewali Mandar Regency - Halim, Didin; Mutmainna, Nur; Guntur, Muhamamd; Purna, Zarni Adia (Jurnal Aktor, 2024)
This study aims to determine how the application of good governance principles in public services in Matakali District, Polewali Mandar Regency. The research method used in this study is qualitative descriptive method. Data sources are obtained from primary data and secondary data, data collection techniques through observation, interviews and documentation. This research uses the theory of good governance principles from Sedarmayanti (2009) based on four indicators to measure the success of good governance principles, namely accountability, transparency, openness and the rule of law. The results of this study show that the application of good governance principles in public services in Matakali District, Polewali Mandar Regency is seen from 4 variables of the application of good governance principles, including: 1. The principle of Accountability has been implemented well, this shows that the officers have carried out their public service duties effectively and responsibly in Matakali District. 2. The principle of transparency in public services is divided into two criteria including ease of obtaining information, indicating that the public has not been able to get broad access to information due to the unavailability of technology-based information centers such as WhatsApp, Instagram, Facebook or supporting websites in Matakali District; and Government openness in providing information services, indicating that the sub-district officials have provided information services openly in Matakali sub-district. 3. The principle of Openness is still not implemented optimally, this shows that there are still informants who do not know the existence of complaint boxes in Matakali District. 4. The rule of law shows that it has been carried out properly by carrying out duties in accordance with SOPs and without discriminating the services provided.